Quem vai arquivar os conteúdos de redes sociais presidenciais no Brasil? - Silva, Anahi Rocha [UNESP]; Vitoriano, Marcia Cristina de Carvalho Pazin (Liinc em Revista, 2025)
The use of online social media platforms as a communication strategy during the presidential administration resulted in a significant number of studies exploring its various aspects and applications. Despite this, research on the production and archiving of content produced by the president in these virtual environments, from the perspective of Information Science and Archival Science, is still limited. The objective is to research the state of the art of institutional policies for archiving presidential communications on social networks in Brazil. was researched on the use of platforms by the head of the nation, with reflections on the importance of these informational resources as primary sources of information. the use of Twitter and YouTube platforms, by President Jair Messias Bolsonaro, was identified and researched on policies for archiving communications in Brazil. Presidential social networks offer extraordinary potential for investigation, allowing us to establish new perspectives on events, analyze facts and contexts with greater clarity. The study indicates that exclusive content was produced for the platforms throughout the term. These gift records, produced by the president, have become irreplaceable documents as a source of evidence and information. And, in the future, this digital legacy should be part of both the personal memory of the head of the nation and the social and collective memory. However, there are indications of the chaotic stage in which Brazil finds itself, and of the risks of posts being deleted or lost, given the absence of specific schedules, policies and standards aimed at capturing, archiving and preserving presidential communications on social networks El uso de plataformas de redes sociales en línea como estrategia de comunicación durante la administración presidencial dio lugar a un número significativo de estudios que exploran sus diversos aspectos y aplicaciones. A pesar de ello, la investigación sobre la producción y archivo de los contenidos producidos por el presidente en estos entornos virtuales, desde la perspectiva de las Ciencias de la Información y la Archivística, es aún limitada. El propósito de este artículo es doble. En primer lugar, reseñamos el uso de las plataformas por parte del jefe de Estado, discutimos y reflexionamos sobre la importancia de estos recursos informativos como fuentes primarias de información. En segundo lugar, identificamos el uso de las plataformas Twitter y Youtube por parte del Presidente de la República, Jair Messias Bolsonaro, e investigamos el estado del arte de las políticas de archivo de estas comunicaciones en Brasil. Las redes sociales presidenciales ofrecen un potencial extraordinario para la investigación, permitiéndonos establecer nuevas perspectivas sobre los hechos, analizar hechos y contextos con mayor claridad. Señalamos que se produjeron contenidos exclusivos para las plataformas y que se convirtieron en documentos insustituibles, como prueba en la reconstrucción de los hechos y en la preservación de la memoria personal del jefe de la nación, de la memoria social y colectiva. Sin embargo, hay indicios de la etapa caótica en la que se encuentra Brasil y los riesgos de que se eliminen o pierdan publicaciones, dada la ausencia de horarios, políticas y estándares específicos destinados a capturar, archivar y preservar las comunicaciones presidenciales en las redes sociales. A utilização das plataformas de redes sociais online como estratégia de comunicação durante a administração presidencial, resultou em um número significativo de estudos explorando seus vários aspectos e aplicações. Apesar disso, pesquisas sobre a produção e o arquivamento de conteúdos produzidos pelo presidente nestes ambientes digitais, sob a perspectiva da Ciência da Informação e da Arquivologia, ainda são limitadas. O objetivo é descobrir qual o estado da arte das políticas institucionais para arquivamento das comunicações presidenciais em redes sociais no Brasil. Delineamos o uso das plataformas pelo chefe da nação, com reflexões acerca da a importância desses recursos informacionais como fontes primárias de informações. Identificamos o uso das plataformas Twitter e Youtube, pelo Presidente Jair Messias Bolsonaro, e pesquisamos sobre políticas para arquivamento dessas comunicações no Brasil. As redes sociais presidenciais oferecem um potencial extraordinário para a investigação, permitindo estabelecer novas perspectivas sobre eventos, analisar fatos e contextos com maior clareza. O estudo indica que foram produzidos conteúdos exclusivos para as plataformas durante todo o mandato. Esses registros do presente, produzidos pelo presidente, tornaram-se documentos insubstituíveis como fonte de provas e informações. E, no futuro, esse legado digital deverá fazer parte, tanto da memória pessoal do chefe da nação, quanto da memória social e coletiva. No entanto, há indicativos do estágio caótico em que o Brasil se encontra, e dos riscos de serem apagadas ou perdidas as postagens, frente à ausência de cronogramas, políticas e padrões específicos voltados à captura, arquivamento e preservação das comunicações presidenciais em redes sociais